1987
DOI: 10.1021/bi00387a003
|View full text |Cite
|
Sign up to set email alerts
|

Cationic metals promote sequence-directed DNA bending

Abstract: A DNA segment of approximately 200 base pairs (bp) from Crithidia fasciculata kinetoplast minicircles was previously shown by electron microscopy (EM) to bend into a small circle due to its unique nucleotide sequence containing repeated blocks of 4-6 A's. When this segment was flanked by 207 bp of plasmid DNA on one side and 460 bp on the other, the resulting 890-bp DNA was found to appear either relatively straight or extremely bent as visualized by EM. The bend was located one-third the distance from one end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
1

Year Published

1988
1988
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 27 publications
3
43
1
Order By: Relevance
“…In the case of the mtr and tyrPϩ3* promoters, the HU-or IHF-mediated DNA bending could affect the promoter activities by introducing ratelimiting steps for transcription initiation. This idea is supported by our finding that BaCl 2 , a chemical compound which is known to induce DNA bending (22), can also cause inhibition of transcription of both the mtr and tyrPϩ3 promoters (results not shown). In vitro studies by Flashner and Gralla (9) have shown that BaCl 2 has the same inhibitory or stimulatory effects on the binding of a number of E. coli regulatory proteins to their DNA targets as HU.…”
Section: Fig 2 (A)supporting
confidence: 60%
“…In the case of the mtr and tyrPϩ3* promoters, the HU-or IHF-mediated DNA bending could affect the promoter activities by introducing ratelimiting steps for transcription initiation. This idea is supported by our finding that BaCl 2 , a chemical compound which is known to induce DNA bending (22), can also cause inhibition of transcription of both the mtr and tyrPϩ3 promoters (results not shown). In vitro studies by Flashner and Gralla (9) have shown that BaCl 2 has the same inhibitory or stimulatory effects on the binding of a number of E. coli regulatory proteins to their DNA targets as HU.…”
Section: Fig 2 (A)supporting
confidence: 60%
“…Changes in DNA conformation can be potentiated by particular cations such as spermidine (15)(16)(17)(18). These polymorphic variations have been detected because ofthe easily measured changes in physical properties associated with the alterations.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro transcriptional analysis using a supercoiled template has shown that transcription from the mtr promoter ( 70 ) is strongly inhibited by histone-like proteins HU and IHF or by BaCl 2 (26). In the presence of any of these reagents, which are known to alter DNA structure (6,13), it is possible to demonstrate activation of transcription by purified TyrR protein and either of the cofactors, phenylalanine and tryptophan (26). The transcription activation of mtr does not occur if the activation-negative TyrR protein RQ10 is substituted for the wild-type protein or if RNA polymerase with a truncated ␣ C-terminal domain is used (26).…”
mentioning
confidence: 99%